Assessment of Magnaporthe grisea mating type by spore PCR - Jin-Rong Xu; John E. Hamer (Fungal Genetics Reports, 1995)
Isolation of DNA from filamentous fungi for PCR analysis is usually time consuming and involves use of toxic chemicals such as phenol/chloroform. In Saccharomyces cerevisiae, PCR assay can be performed with yeast colonies (Huxley et al. TIG 1990 6:236). Here we describe a PCR protocol which uses M. grisea conidia directly for PCR analysis without extraction of DNA.